Comparison of in Silico, Electrochemical, in Vitro and in Vivo Metabolism of a Homologous Series of (Radio)fluorinated σ1 Receptor Ligands Designed for Positron Emission Tomography. (28th September 2016) - Wiese, Christian; Große Maestrup, Eva; Galla, Fabian; Schepmann, Dirk; Hiller, Achim; Fischer, Steffen; Ludwig, Friedrich‐Alexander; Deuther‐Conrad, Winnie; Donat, Cornelius K.; Brust, Peter; Büter, Lars; Karst, Uwe; et al.
Abstract: The imaging of σ1 receptors in the brain by fluorinated radiotracers will be used for the validation of σ1 receptors as drug targets as well as for differential diagnosis of diseases in the central nervous system. The biotransformation of four homologous fluorinated PET tracers 1′‐benzyl‐3‐(ω‐fluoromethyl to ω‐fluorobutyl)‐3 H ‐spiro[2]benzofuran‐1, 4′‐piperidine] ([ 18 F]1 –4 ) was investigated. In silico studies using fast metabolizer (FAME) software, electrochemical oxidations, in vitro studies with rat liver microsomes, and in vivo metabolism studies after application of the PET tracers [ 18 F]1 –4 to mice were performed. Combined liquid chromatography and mass spectrometry (HPLC–MS) analysis allowed structural identification of non‐radioactive metabolites. Radio‐HPLC and radio‐TLC provided information about the presence of unchanged parent radiotracers and their radiometabolites. Radiometabolites were not found in the brain after application of [ 18 F]2 –4, but liver, plasma, and urine samples contained several radiometabolites. Less than 2 % of the injected dose of [ 18 F]4 reached the brain, rendering [ 18 F]4 less appropriate as a PET tracer than [ 18 F]2 and [ 18 F]3 . Compounds [ 18 F]2 and [ 18 F]3 possess the most promising properties for imaging of σ1 receptors in the brain. High σ1 affinity ( K i =0.59 nm ), low lipophilicity (log D 7.4 =2.57), high brain penetration (4.6 % of injected dose after 30 min), and the absence of radiometabolites in the brain favor the fluoroethyl derivative [ 18 F]2 slightly over the fluoropropyl derivative [ 18 F]3 for human use. Abstract : Taking a close look : The biotransformation of a homologous series of fluoroalkyl‐substituted σ1 receptor ligands designed as PET tracers was investigated at different levels: in silico using FAME software, electrochemically, in vitro, and in vivo. Electrochemical oxidation and in vitro studies with rat liver microsomes combined with LC–MS analysis allowed identification of the metabolite structure. The nature and amount of radiometabolites in various tissues were analyzed by radio‐HPLC and radio‐TLC after application of the [ 18 F]‐labeled PET tracers to mice.